2018
DOI: 10.1016/j.jmgm.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Strong C H/O interactions between polycyclic aromatic hydrocarbons and water: Influence of aromatic system size

Abstract: Energies of CH/O interactions between water molecule and polycyclic aromatic hydrocarbons with a different number of aromatic rings were calculated using ab initio calculations at MP2/cc-PVTZ level. Results show that an additional aromatic ring in structure of polycyclic aromatic hydrocarbons significantly strengthens CH/O interactions. Calculated interaction energies in optimized structures of the most stable tetracene/water complex is -2.27 kcal/mol, anthracene/water is -2.13 kcal/mol and naphthalene/water i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For example, in the Gulf of Mexico Seawater the concentrations of PAHs were about 8 times higher in the surface water (0–1 m) compared to deep water (10–200 m) (Boehm et al, ). Indeed, theoretical calculations performed at a molecular level indicate that the interfacial region provides an energetic sink for the enrichment of PAHs (Vacha et al, ; Veljković, ). The interfacial region, although only a few Angstroms thin, plays an important role for the enhanced photodegradation of PAHs at the SML compared to the bulk, as the highest concentrations of PAHs (Carpenter & Nightingale, ; Liss & Duce, ), as well as the highest intensity of Ultraviolet–visible (UV‐VIS) light that occurs at the SML (Li et al, ; Vasilkov et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Gulf of Mexico Seawater the concentrations of PAHs were about 8 times higher in the surface water (0–1 m) compared to deep water (10–200 m) (Boehm et al, ). Indeed, theoretical calculations performed at a molecular level indicate that the interfacial region provides an energetic sink for the enrichment of PAHs (Vacha et al, ; Veljković, ). The interfacial region, although only a few Angstroms thin, plays an important role for the enhanced photodegradation of PAHs at the SML compared to the bulk, as the highest concentrations of PAHs (Carpenter & Nightingale, ; Liss & Duce, ), as well as the highest intensity of Ultraviolet–visible (UV‐VIS) light that occurs at the SML (Li et al, ; Vasilkov et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the C(sp 2 )-H/π and π-π interactions are similar in TS5 p and TS5 o , the former contains an extra C(sp 3 )-H/π interaction at 3.29 Å, as well as a significant C(sp 2 )-H⋯O interaction considering that this C-H group belongs to a polycyclic aromatic hydrocarbon. 41 These two additional noncovalent interactions in TS5 p result directly from the orientation of S2 toward the Cu(I) complex, which is induced by the para-substitution. The π-interactions in TS5 o and TS5 m are comparable, and their relative energies can be understood with reference to the electronic bias from the different natural charges on the ortho-C and meta-C atoms.…”
Section: Regioselectivity Of C-f Bond Substitutionmentioning
confidence: 99%
“…In our previous study, we showed that the addition of aromatic rings strengthens C–H/O interactions formed between aromatic hydrocarbons and the water molecule and that the main reason for this is increased polarization which leads to more positive values of electrostatic potentials over hydrogen atoms from C–H fragments. 22 Since positive values of electrostatic potential in the central regions of HEM molecules are an indicator of their sensitivities towards detonation, changing the aromatic system size could be used as a tool in the design of new polycyclic aromatic HEM molecules.…”
Section: Introductionmentioning
confidence: 99%